Are we there or do we have more to do? Metaverse in facility management and future prospects - El Jaouhari, Asmae; Arif, Jabir; Samadhiya, Ashutosh; Kumar, Anil; Trinkūnas, Vaidotas (International Journal of Strategic Property Management, 2023)
Businesses are eager to adopt new technologies such as augmented reality, blockchain, extended reality, and artificial intelligence, among others, as they see beneficial applications for strategic empowerment. As one of the technological disruptions, metaverse has caught the attention of the larger business community and facility management (FM) sector. In a world where various virtual realities converge, the hyper-connected digital universe known as the metaverse has the potential to fundamentally alter how FM and business interactions are conducted in the future. More people are spending time conducting business online, increasing the metaverse’s potential. Businesses are also making significant investments in the development of metaverse techniques. This study reviews the current literature to comprehend how metaverse techniques have shaped the building blocks of FM by looking at 206 papers. There is currently a dearth of functional metaverse research. This article aims to provide a thorough analysis of the integration of metaverse techniques for facility management. The review reveals several opportunities for further research into the FM-metaverse ecosystem, including improving data interoperability, enhancing the precision of point cloud data for as-built models of existing facilities, and producing efficient virtual property database integration.